Express housekeeping how to speed clean, lighten the laundry load, cleaning tricks & tips - Shepard, Anna (New York, NY DK Pub, 2011)
Offers advice and routines to speed clean every room in the house as well as tips for cleaning up after children and pets.--
Introduction -- Speed cleaning -- Doing dishes -- Clothes and laundry -- Removing stains -- Coping with children and pets -- Decluttering
Includes index
Keywords: Home economics; House cleaning; Housekeeping